Overview of biomass pretreatment for cellulosic ethanol production - Zheng, Yi; Pan, Zhongli; Zhang, Ruihong (International Journal of Agricultural and Biological Engineering, 2009)
Bioconversion of lignocellulosic biomass to ethanol is significantly hindered by the structural and chemical complexity of biomass, which makes these materials a challenge to be used as feedstocks for cellulosic ethanol production. Cellulose and hemicellulose, when hydrolyzed into their component sugars, can be converted into ethanol through well established fermentation technologies. However, sugars necessary for fermentation are trapped inside the crosslinking structure of the lignocellulose. Hence, pretreatment of biomass is always necessary to remove and/or modify the surrounding matrix of lignin and hemicellulose prior to the enzymatic hydrolysis of the polysaccharides (cellulose and hemicellulose) in the biomass. Pretreatment refers to a process that converts lignocellulosic biomass from its nativ form, in which it is recalcitrant to cellulase enzyme systems, into a form for which cellulose hydrolysis is much more effective. In general, pretreatment methods can be classified into three categories, including physical, chemical, and biological pretreatment. The subject of this paper emphasizes the biomass pretreatment in preparation for enzymatic hydrolysis and microbial fermentation for cellulosic ethanol production. It primarily covers the impact of biomass structural and compositional features on the pretreatment, the characteristics of different pretreatment methods, the pretreatment study status, challenges, and future research targets. Keywords: lignocellulosic biomass, pretreatment, cellulosic ethanol, enzymatic hydrolysis, fermentation, cellulose, hemicellulose, lignin DOI: 10.3965/j.issn.1934-6344.2009.03.051-068 Citation: Yi Zheng, Zhongli Pan, Ruihong Zhang. Overview of biomass pretreatment for cellulosic ethanol production. Int J Agric & Biol Eng, 2009; 2(3): 51